2014
DOI: 10.1097/hjh.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Elevated systolic blood pressure during recovery from exercise and the risk of sudden cardiac death

Abstract: This study shows that SBP during recovery phase from exercise is related to the risk of SCD, although its prognostic value is limited in conjunction with the assessment of resting SBP in the general male population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…As an alternative, we should be cautious with exercise intensity so as to circumvent cardiovascular problems after exercise in this population. This is reinforced by a previous study conducted by Laukkanen (Laukkanen et al 2014), which stated that abnormal cardiovascular recovery following exercise is related to risk of sudden cardiac death. Bearing this in mind, we highlighted the theory that subjects with HADS>12 (viable anxiety or depression) would display delayed autonomic recovery following exercise.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…As an alternative, we should be cautious with exercise intensity so as to circumvent cardiovascular problems after exercise in this population. This is reinforced by a previous study conducted by Laukkanen (Laukkanen et al 2014), which stated that abnormal cardiovascular recovery following exercise is related to risk of sudden cardiac death. Bearing this in mind, we highlighted the theory that subjects with HADS>12 (viable anxiety or depression) would display delayed autonomic recovery following exercise.…”
Section: Introductionmentioning
confidence: 78%
“…Our study affords important data for subjects with high levels of anxiety or depression evaluated through the HADS. Previously, Laukkanen et al (Laukkanen et al 2014) suggested that higher values of SAP during recovery from exercise is connected with increased risk of sudden cardiac death. The authors examined 2366 men between 42 and 61 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed heart rate (HR) recovery (HRR) is associated with impaired prognosis in patients with CAD [10][11][12] and T2D [13,14]. Also, high systolic blood pressure (SBP) during recovery has been associated with risk for cardiovascular morbidities without assessment of the SBP change during recovery in these studies [15][16][17]. Among patients referred to exercise testing, SBP recovery/peakratio was a potent predictor of death but not independently of HRR [18].…”
Section: Introductionmentioning
confidence: 94%
“…All hospital documents, including medical records, laboratory and ECG findings from hospital and paramedical staff, and the use of medications and defibrillators, were available to use. 10 All deaths that occurred by the end of 2014 were checked against the hospital documents, health center wards, and death certificates. There were no losses to follow-up.…”
Section: Accepted Manuscriptmentioning
confidence: 99%